Estimate inpatient’s cost of breast cancer treatment for a single episode of care - Lau, Huan Yee; Norlia Abdullah; Hilawati Yusof; Noriza Majid (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Malaysia, breast cancer remains the leading cause of cancer-related mortality. The cost of breast cancer treatment has been noted as a major barrier to care. The community and the healthcare system as a whole would benefit from knowing the cost of treating this illness. The goal of this study is to identify the factors that contribute to the high cost of breast cancer treatment and provide an estimate of those costs. As a result, between 2017 and 2021, a total of 1027 samples were collected from breast cancer patients at Hospital Canselor Tuanku Muhriz’s (HCTM) Breast & Endocrine Unit (ENB) and International Casemix and Clinical Coding Centre (ITCC). Information gathered consists of total healthcare expenditures for a single episode of care, patient demographics like age and gender, and clinical details like disease severity, hospitalisation duration, comorbidities, metastatic status, treatments administered, and discharge status. Regression analysis was used in this research. Because treatment costs tend to be skewed, a logarithmic transformation is used to produce a more precise model for estimating those costs. The results show that age, severity, treatment, length of hospitalisation, hypertension, lung, lymph, and brain metastases, and hospital discharge status all have an impact on the total cost of treating breast cancer patients. Treatment costs are not significantly affected by the presence of liver and bone metastases or comorbidities such as cardiovascular disease, high cholesterol, or diabetes.